MODEL PEMBELAJARAN CENTERS BASED LEARNING UNTUK TINGKATKAN KRITIS DAN KEMANDIRIAN SISWA KELAS 1 SD - Riska Pristiani; Eka Fitriani; Novita Nurul Azizah; Tara Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The implementation of learning models still requires various developments and improvements. Therefore, one of the researcher's efforts to support the teaching and learning process carried out by teachers is to develop effective learning models for improving skills. This study aims to produce a centers-based learning model for the material of adding numbers 1-20 in grade 1 of elementary school to improve critical thinking and independence skills and to test the effectiveness of the learning model through the results of assessing students' skills. The development uses the Research and Development method with the ADDIE approach (Analysis, Design, Develop, Implement, Evaluate). The subjects of this study were grade 1 students (A, B, C) consisting of 63 students from SD Kristen Charis Kota Malang. The results of the study showed that this learning model was effective in improving students' critical thinking and independence skills, as shown by the results of very suitable/suitable validation, and an increase in each category in each aspect improved except for the very low category for critical thinking skills and the not yet visible category for independence aspects.